Beliefs, fear and awareness of women about breast cancer: Effects on mammography screening practices. Issue 2 (20th November 2020) - Emami, Lida; Ghahramanian, Akram; Rahmani, Azad; Mirza Aghazadeh, Ahmad; Onyeka, Tonia C.; Nabighadim, Amirreza
Abstract: Aim: This study sought to investigate the beliefs, fear and awareness about breast cancer and mammography screening practices of women in Iran. Methods: This descriptive‐correlational study was conducted at Tabriz, East Azerbaijan Province, northwest of Iran from February–July 2017. One hundred and fifty‐two women aged 40 years and older, who were referred to 12 health centres for health services were selected via clustering sampling. Associations between variables and mammography screening practices were examined using bivariate and multivariate logistic regression analyses. Participants who had a mammogram within the last 24 months were compared with those who had none. Sociodemographic questionnaire, Champion's Breast Cancer Fear Scale, Champion's Health Belief Model Scale for Mammography Screening, Breast Cancer Awareness Scale and Powe Fatalism Inventory were the tools used for data gathering. Results: Just 38.2% of women reported having a mammogram within the last 24 months. Self‐efficacy (OR = 5.36, B = 1.68, p < .001), susceptibility (OR = 2.83, B = 1.04, p < .001), motivation (OR = 2.11, B = 0.75, p = .024) and lower perceived barriers (OR = 0.25, B = −1.37, p < .001) were associated with being screened. Neither fatalistic belief nor awareness towards breast cancer was significant.